2018
DOI: 10.1016/j.trci.2018.06.013
|View full text |Cite
|
Sign up to set email alerts
|

Persistence and adherence to rivastigmine in patients with dementia: Results from a noninterventional, retrospective study using the National Health Insurance research database of Taiwan

Abstract: IntroductionThe objective of the study was to assess adherence and persistence of patients treated with rivastigmine versus donepezil.MethodsPersistence was calculated as the time from the first prescription date of rivastigmine/donepezil until discontinuation/medication switch/end of available data, whichever occurred first. Adherence was calculated as proportion of days covered and medication possession ratio.ResultsA majority of patients persisted on 4.5 and 6 mg of rivastigmine for 429 and 468 days, respec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 22 publications
1
10
0
Order By: Relevance
“…Nearly 20% of patients did not fill further prescription after one month both in the donepezil and rivastigmine groups, the ratio being similar as seen in Austria (14%) [ 15 ]. Differently from previous studies [ 11 , 24 , 25 ], where the follow-up of patients was stopped after their drug discontinuations (gaps), we followed discontinuing patients and found that the majority of them returned to ChEi-therapy with a partial or good adherence, which finding is of practical importance in clinical practice.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Nearly 20% of patients did not fill further prescription after one month both in the donepezil and rivastigmine groups, the ratio being similar as seen in Austria (14%) [ 15 ]. Differently from previous studies [ 11 , 24 , 25 ], where the follow-up of patients was stopped after their drug discontinuations (gaps), we followed discontinuing patients and found that the majority of them returned to ChEi-therapy with a partial or good adherence, which finding is of practical importance in clinical practice.…”
Section: Discussionmentioning
confidence: 69%
“…In our study, there were fifteen times more donepezil users than rivastigmine. In Poland, donepezil use was three times more common [ 24 ], while in Taiwan and Austria the ratio was even more balanced; donepezil was used only 1.4 and 1.16 times more than rivastigmine, respectively [ 15 , 25 ]. The considerable difference in Hungary may be partially due to the fact that donepezil is available in several generic forms in contrast to rivastigmine, which is marketed as an originator only, resulting in considerably higher monthly therapeutic expenses.…”
Section: Discussionmentioning
confidence: 99%
“…A decline of 2.3 points per year in MMSE scores has been observed in those who progressed to dementia without treatment [19]. Per the National Health Insurance regulations in Taiwan, patients with AD using reimbursed rivastigmine should switch to another treatment if the MMSE score decreases by more than two points [13]. During the follow-up period, patients treated with the 10 cm 2 rivastigmine patch maintained cognitive performance, and only one patient had to withdraw from the study due to a failure in re-submission for health insurance reimbursement; however, the reason for the failure was not specified.…”
Section: Discussionmentioning
confidence: 99%
“…The overall persistence and adherence to rivastigmine (oral and the 5 cm 2 patch) versus donepezil in the Taiwanese population was recently reported using the national health dataset [13]. The real-world treatment efficacy of the 10 cm 2 rivastigmine patch in patients with AD has still not been extensively reported.…”
Section: Introductionmentioning
confidence: 99%
“…Chang et al [17] and Hinkin et al [13] suggested that non-adherence may have multiple clinical consequences in addition to cognitive decline. Hinkin [13] also stated that being adherent resulted in a slower decline of multiple cognitive functional and global outcome measures.…”
Section: Mental Illness 4 Simplyoccasionally Forgetting To Take Their Medicationmentioning
confidence: 99%